The Importance of Syntax in Understanding English Sentence Structure - Raihana, Ariqqah; Harahap, Afzylianur; Dalimunte, Alya Fadhillah; Elvida Futri Mahara; Lubis, Nurul Hidayah; Ismahani, Siti (Innovative: Journal Of Social Science Research, 2024)
This research explores the role of syntax in English language learning, particularly for non-native speakers. Using a literature review method, 12 academic journals published between 2019-2024 were reviewed through Google Scholar and ResearchGate, with 3 meeting the selection criteria. The study analyzes sentence structures, including simple and complex patterns, idioms, and their cultural connections. Syntax involves elements like subjects, predicates, objects, clauses, and phrases, and how these elements work together to form meaning. The research shows that mastering syntax improves sentence construction, enhances communication, and helps learners navigate English’s complexity. It also highlights the importance of syntax in understanding idioms and complex sentence structures in both formal and informal contexts. Mastery of syntax is crucial for effective language learning and supports the development of comprehensive language skills.